Bahasa, Agama, dan Kesadaran Lingkungan: Analisis Konseptual Peran Diskursus Keagamaan dalam Penguatan Ekonomi Berbasis Ekologi - Umar Mukhtar Siregar; Hidayat Herman (Management Studies and Business journal, 2025)
Environmental issues and sustainability cannot be separated from the ways societies construct meaning and values through language. In religious societies, religious discourse plays a strategic role in shaping collective environmental awareness and influencing related social practices. This article aims to conceptually analyze the role of language and religious discourse in constructing environmental awareness and its implications for ecology-based socio-economic practices. The study employs a library research method using a critical-conceptual approach to national and international literature on discourse analysis, ecolinguistics, and studies of religion and environment. The findings indicate that religious language functions as a medium of moral legitimation that frames human–nature relationships through narratives, metaphors, and normative categories. Religious discourse emphasizing responsibility, balance, and environmental care contributes to the formation of a more stable and collective ecological awareness. Such awareness can subsequently be translated into social practices, including ecology-based economic activities, which are understood as forms of social praxis culturally and symbolically legitimized through language. This article highlights that linguistic approaches, particularly critical discourse analysis and ecolinguistics, offer significant contributions to understanding religious language as a cultural foundation for social transformation toward environmental sustainability.